Sinonasal malignancies with neuroendocrine differentiation: Case series and review of literature - Menon Santosh; Pai Prathamesh; Sengar Manju; Aggarwal J; Kane Shubhada (Wolters Kluwer Medknow Publications, 2010)
Primary sinonasal tumors with neuroendocrine differentiation (SCND) are uncommon tumors with considerable overlap of histological features. Based on their neuroendocrine differentiation they can be sub categorized into sinonasal undifferentiated carcinoma (SNUC), sinonasal neuroendocrine carcinoma (SNEC), esthesioneuroblastoma (ENB) and small cell carcinoma (SmCC). The natural history and biological behavior varies in this group of tumors. Hence the histo-morphological diagnosis coupled with grading/staging is important for the prognostication of these tumors. Aim : To study the clinicopathological characteristics of sinonasal neuroendocrine malignancies at our institute. Material and Methods : We searched our institute′s pathology database for the period from 2002 to 2007, for the four subcategories of sinonasal tumors with neuroendocrine differentiation. Morphological and immunohistochemical features were studied and, grading, staging was done in accordance with standard criteria. The clinical treatment and follow- up data were retrieved from the case files in available cases. Results : A total of 37 cases were retrieved from our database which include 14 cases of SNUC, 14 cases of ENB and nine cases of SNEC. The cases of SNUC were immunopositive for cytokeratin, epithelial membrane antigen and weakly for neuron-specific enolase. SNEC showed strong reactivity with epithelial and neuroendocrine markers whereas ENB demonstrated immunoreactivity to synaptophysisn and chromogranin strongly, with weak to negative expression of epithelial markers. All cases of SNUC and SNEC were of high grade and stage whereas 50% of ENB cases were of grade II but high stage tumors. Most of the SNUC and SNEC patients had been treated with multimodality treatment regimens including upfront chemotherapy followed by surgery and loco- regional radiation. In contrast, ENB patients had undergone surgical extirpation followed by radiation therapy in majority of cases. With limited follow-up data, it was observed that four out of five SNUC patients and three out of four SNEC patients developed either loco-regional (three of SNUC and two of SNEC) or distant metastasis (one patient each of SNUC and SNEC). ENB patients also had loco-regional recurrences (five out of seven patients) with a more protracted course but no distant metastases were observed during the follow up in available cases. Conclusion : Sino nasal tumors with neuroendocrine differentiation are a heterogenous group of tumors with overlapping histo-morphological features. They can be distinguished based on immunohistochemical characteristics. Pathological sub categorization is imperative for management and prognostication of these aggressive tumors.